Contribution of Agriculture and Poverty Eradication Programme in Economic Development of India - Sinha, Nand Kishore (Journal of Commerce and Trade, 2020)
The paper first reviews the past contributions of agricultural research to poverty alleviation, as seen through a variety of studies, including village studies. These studies show that Green Revolution technologies were effective in reducing poverty, but their impact on the poor was moderate and after a considerable time lag. Poverty is an important concern for most of the developing countries. Both the agriculture and non-agriculture sector plays an important role in reducing poverty. But in case of agrarian economy like India, the contribution of agriculture in poverty reduction is dominant since the majority of poor people are relied on this sector for their sustenance. Although economic growth leads to poverty reduction but the sector mix of growth matters substantively. The most widely accepted view is that it contributes to economic growth and economic growth is directly related to poverty alleviation. Government of India launched several poverty eradication programmes to create assets that benefit the poor and by raising the productivity of the poor through education, public health and other human resource related measures. This research paper also examines the overviews of poverty eradication programmes implemented in India. From the study, it is clear that the Government have been attempting the eradication of the poverty through multi dimensional approaches. Even though the Government plays a major role the implementation of the programmes the success yet vests with the public private partnership where the role and commitment of the private beneficiaries without whom the projects would not success.